Prominent premaxilla management on bilateral cleft lip and palate - Tatiana Izchel Castillo Torres; María Luisa Peralta Pedrero; Juan Arturo Cuellar Dodd; Cristhian Alexis Lara Robledo; Mónica Dominguez Martìnez (Wolters Kluwer Medknow Publications, 2019)
The treatment cleft lip and palate (CLP) should start at an early age with a multidisciplinary team and with a comprehensive approach. The aim of the management of protruded premaxilla in patients with bilateral CLP is to relocate the premaxilla to achieve surgical closure of the lip. The objective of the case report is to present the surgical-orthodontic treatment for the surgical reposition of the protruded premaxilla in a 3-year-old patient with BCLP. A patient of 3 years old with BCLP his treatment plan is a surgical reposition of the premaxilla and posterior closure of the primary lip. The surgical reposition of the premaxilla was made planning the osteotomy with dental casts. After 6 months of starting the surgical-orthodontic treatment, the patient meets bilateral lip closure satisfactorily without reported complications. Planning of the treatment allows performing a procedure that reduces the likelihood of complications and achieving the closing of the lip to reestablish the function, anatomy, and esthetics.